Exploring the nature of ecological specialization in a coral reef fish community: Morphology, diet and foraging microhabitat use - Brandl, S.; Robbins, William; Bellwood, D. (The Royal Society Publishing, 2015)
© 2015 The Author(s) Published by the Royal Society. All rights reserved.Patterns of ecological specialization offer invaluable information about ecosystems. Yet, specialization is rarely quantified across several ecological niche axes and variables beyond the link between morphological and dietary specialization have received little attention. Here, we provide a quantitative evaluation of ecological specialization in a coral reef fish assemblage (f. Acanthuridae) along one fundamental and two realized niche axes. Specifically, we examined ecological specialization in 10 surgeonfish species with regards to morphology and two realized niche axes associated with diet and foraging microhabitat utilization using a recently developed multidimensional framework. We then investigated the potential relationships between morphological and behavioural specialization. These relationships differed markedly from the traditional ecomorphological paradigm. While morphological specialization showed no relationship with dietary specialization, it exhibited a strong relationship with foraging microhabitat specialization. However, this relationship was inverted: species with specialized morphologies were microhabitat generalists, whereas generalized morphotypes were microhabitat specialists. Interestingly, this mirrors relationships found in plant–pollinator communities and may also be applicable to other ecosystems, highlighting the potential importance of including niche axes beyond dietary specialization into ecomorphological frameworks. On coral reefs, it appears that morphotypes commonly perceived as most generalized may, in fact, be specialized in exploiting flat and easily accessible microhabitats.